STUDI PEMIKIRAN PENERAPAN TAX EARMARKING PADA BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI KOTA MALANG - Hidayat, Kadarisman; Mayowan, Yuniadi; Almaghfi, Lofie Bachtiar (Jurnal Mahasiswa Perpajakan, 2016)
This research is aimed to deliver a contribution to the application of tax earmarking in Malang City. Tax Earmarking is a regulation that requires the allocation of several tax revenues to be used in specific project or other public service as stated in Law No.29/2008 about Local tax and Local Retribution. The application of tax earmarking is designated to improve a service needed by community. Other benefit from tax earmarking application is the increased accountability of local government in allocating tax revenue to satisfy what has been needed by the community. The idea to imply the taxation against the Entitlement Duty of BPHTB is to maximizing tax earmarking application in Malang City. Based on the result of research, it is concluded that tax earmarking application to BPHTB is plausible in Malang City. A local regulation is needed to arrange tax earmarking in Malang City. It may be suggested that the local government of Malang City shall accommodate tax earmarking regulation into the budgeting system to improve the accountability of budget usage in Malang City. Keywords: Tax Earmarking, BPHTB, Budgeting System Â  ABSTRAK Tax Earmarking merupakan sebuah peraturan yang mewajibkan pengalokasian penerimaan beberapa jenis pajak untuk digunakan secara khusus proyek atau pelayanan publik lainnya yang tercantum dalam UU No 29 Tahun 2008 tentang Pajak Daerah dan Retribusi Daerah. Tujuan diterapkannya peraturan tax earmarking ini adalah untuk meningkatkan pelayanan yang dibutuhkan oleh masyarakat, manfaat lain yang bisa didapatkan dari penerapan tax earmarking ini adalah meningkatkan akuntabilitas pemerintah daerah dalam mengalokasikan penerimaan pajak sehingga sesuai dengan kebutuhan masyarakat. Pemberian ide pemikiran untuk menambahkan jenis pajak BPHTB dimaksudkan untuk memaksimalkan penerapan tax earmarking di Kota Malang. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan tax earmarking pada BPHTB sangat mungkin untuk dilakukan dan diterapkan di Kota Malang dan dibutuhkan sebuah peraturan daerah yang mengatur tentang tax earmarking di Kota Malang dan Pemerintah Daerah Kota Malang diharapkan dapat mengakomodir peraturan tax earmarking kedalam sistem penganggarannya agar meningkatkan akuntabilitas penggunaan anggaran di Kota Malang. Kata Kunci: Tax Earmarking, BPHTB, Sistem Anggaran Â